Teacher research: What exactly are we talking about? - Borg, Simon (Onestopenglish)
Research is often promoted as a powerful form of professional development for teachers. This article by Simon Borg is intended to prompt debate around the topic of teacher research and even inspire you to think about how research could contribute to your own professional development.